2019
DOI: 10.1007/978-3-030-34644-7_25
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Relationship Between Personality and Strategy Formation Using Market Farmer: Using a Bespoke Computer Game in Behavioural Research

Abstract: A computer game was designed for use in a study examining the relationship between facets of the personality trait openness to experience and exploration of a dynamic environment where initial knowledge is limited. A total of 38 females and 56 males aged between 18 and 62 completed a measure of openness to experience and exploration-exploitation before playing Market Farmer: a game specifically designed to engage players and record strategy formation behaviour over time. As expected, exploration increased init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Above all, the existing literature has predominantly focused on the externalities of land transfer [84,85], poverty reduction mechanisms [86][87][88], and market mechanisms among farmers [89,90]. Wu et al conducted a study using data from 2011 to 2014 in rural China, which revealed that farmer participation in land transfer led to a significant reduction in fertilizer application intensity in a grain-growing region in Western China [91].…”
Section: Impact Of Land Transfer Behavior (Str) On Farmers' Livelihoo...mentioning
confidence: 99%
“…Above all, the existing literature has predominantly focused on the externalities of land transfer [84,85], poverty reduction mechanisms [86][87][88], and market mechanisms among farmers [89,90]. Wu et al conducted a study using data from 2011 to 2014 in rural China, which revealed that farmer participation in land transfer led to a significant reduction in fertilizer application intensity in a grain-growing region in Western China [91].…”
Section: Impact Of Land Transfer Behavior (Str) On Farmers' Livelihoo...mentioning
confidence: 99%